Effect of testosterone and its antagonists on knee range of motion through RXFP1 and RXFP2 regulation in rat model - Dehghan, F.; Muniandy, S.; Yusof, A.; Salleh, N. (Federation of American Society of Experimental Biology, 2014)
Objective: To elucidate the testosterone hormone influences on knee joint range of motion (ROM), and the suppressory role of its antagonists; flutamide and finasteride on relaxin receptors in the patellar tendon and collateral ligament. Methods: forty-two ovariectomized females Wistar Kyoto (WKY) rats 8-10 weeks, 180-200g of weight were distributed into seven groups. Peanut oil as a control, testosterone hormone (125 & 250 μg/kg), flutamide (10 mg/kg), and finasteride (20 mg/kg) separately in presence of two testosterone doses were injected subcutaneously for three consecutive days. The antagonists were administrated 30 minutes before the testosterone injection. Following the treatment administrations, the relationships of knee ROM and RXFP1/ RXFP2 mRNA and protein in knee tissues were investigated. Results: Our data showed that knee ROM was significantly decreased in the testosterone treated groups and increased in the presence of flutamide and finasteride, independently. These two antagonists had similar effect on RXFP1 and RXFP2 expression in patellar tendon and collateral ligament. However, finasteride and flutamide blocked testosterone in both doses and increased RXFP1 and RXFP2 expression. Conclusion: This study suggests that testosterone hormone is possibly a primary mediator of RXFP1 and RXFP2 receptors to reduce knee ROM. Nonetheless, flutamide and finasteride revealed inhibitory effect on testosterone thus changed the expression of RXFP1 and RXFP2 receptors in patellar tendon and lateral collateral ligament, inequitably.